2011
DOI: 10.1073/pnas.1102128108
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the affinity of aminoacyl-tRNA to elongation factor Tu for optimal decoding

Abstract: To better understand why aminoacyl-tRNAs (aa-tRNAs) have evolved to bind bacterial elongation factor Tu (EF-Tu) with uniform affinities, mutant tRNAs with differing affinities for EF-Tu were assayed for decoding on Escherichia coli ribosomes. At saturating EF-Tu concentrations, weaker-binding aa-tRNAs decode their cognate codons similarly to wild-type tRNAs. However, tighter-binding aa-tRNAs show reduced rates of peptide bond formation due to slow release from EF-Tu•GDP. Thus, the affinities of aa-tRNAs for EF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 48 publications
11
123
0
1
Order By: Relevance
“…In the tRNA Phe case, the similar k dip values in the WT and W1 cases (Table S1) are much smaller than the maximal rate of peptide bond formation (26) and must therefore reflect similar k cat /K m values for the reaction. We suggest that the significantly smaller k dip values for the "strong" T1 and T2 variants in relation to the WT and W1 variants reflect slow release of EF-Tu·GDP from the ribosome, as previously proposed (23). In the tRNA Glu case, the k dip value is similar among the WT, T1, and T2 variants, reflecting similar k cat /K m values for peptide bond formation.…”
Section: Mechanistic Model Of a Two-step Proofreading Mechanism Insupporting
confidence: 58%
See 2 more Smart Citations
“…In the tRNA Phe case, the similar k dip values in the WT and W1 cases (Table S1) are much smaller than the maximal rate of peptide bond formation (26) and must therefore reflect similar k cat /K m values for the reaction. We suggest that the significantly smaller k dip values for the "strong" T1 and T2 variants in relation to the WT and W1 variants reflect slow release of EF-Tu·GDP from the ribosome, as previously proposed (23). In the tRNA Glu case, the k dip value is similar among the WT, T1, and T2 variants, reflecting similar k cat /K m values for peptide bond formation.…”
Section: Mechanistic Model Of a Two-step Proofreading Mechanism Insupporting
confidence: 58%
“…We found that proofreading amplification of the accuracy of codon reading by aa-tRNAs, F, increases linearly with the affinity (K A value) of aa-tRNAs to EF-Tu·GTP (Fig. 5) when K A is varied by T-stem mutations (23). From this finding, we propose that EF-Tu plays a fundamental role not only in initial codon selection by ternary complex in the GTP conformation but also in the rechecking of the initial codon choice in a proofreading step following GTP hydrolysis on EF-Tu, Pi release, and conformational change of the factor (Fig.…”
Section: Discussion Major Conclusion: Two Proofreading Steps In Bactementioning
confidence: 98%
See 1 more Smart Citation
“…The equilibrium dissociation constant (K D ) was measured in buffer A as described in Sanderson and Uhlenbeck (20). The apparent rate of GTP hydrolysis was performed in buffer B (50 mM Hepes (pH 7.0), 30 mM KCl, 70 mM NH 4 Cl, 10 mM MgCl 2 , and 1 mM DTT) with 1 M ribosomes as described in Schrader et al (22). The rate of dipeptide formation (k pep ) was performed in buffer B as described in Schrader et al (22).…”
Section: Methodsmentioning
confidence: 99%
“…The apparent rate of GTP hydrolysis was performed in buffer B (50 mM Hepes (pH 7.0), 30 mM KCl, 70 mM NH 4 Cl, 10 mM MgCl 2 , and 1 mM DTT) with 1 M ribosomes as described in Schrader et al (22). The rate of dipeptide formation (k pep ) was performed in buffer B as described in Schrader et al (22). The ternary complex binding assay was performed in buffer B as described in Ledoux and Uhlenbeck (23).…”
Section: Methodsmentioning
confidence: 99%